2017
DOI: 10.3389/fpsyg.2017.02039
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Phonological and Morphological Awareness As Longitudinal Predictors of Early Reading and Spelling Development in Greek

Abstract: Different language skills are considered fundamental for successful reading and spelling acquisition. Extensive evidence has highlighted the central role of phonological awareness in early literacy experiences. However, many orthographic systems also require the contribution of morphological awareness. The goal of this study was to examine the morphological and phonological awareness skills of preschool children as longitudinal predictors of reading and spelling ability by the end of first grade, controlling f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
57
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 74 publications
9
57
1
5
Order By: Relevance
“…The absence of PA in first grade supplies further support for previous evidence in Hebrew ( Shatil and Share, 2003 ) and Greek ( Georgiou et al, 2008 ). However, MA was found to be a predictor in third grade, although we concluded that it has a stronger role in opaque orthographies than in transparent orthographies ( Kirby et al, 2012 ; Desrochers et al, 2017 ; Diamanti et al, 2017 ; Manolitsis et al, 2017 ).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The absence of PA in first grade supplies further support for previous evidence in Hebrew ( Shatil and Share, 2003 ) and Greek ( Georgiou et al, 2008 ). However, MA was found to be a predictor in third grade, although we concluded that it has a stronger role in opaque orthographies than in transparent orthographies ( Kirby et al, 2012 ; Desrochers et al, 2017 ; Diamanti et al, 2017 ; Manolitsis et al, 2017 ).…”
Section: Discussioncontrasting
confidence: 56%
“…In the study conducted by Desrochers et al (2017) , MA also predicted word reading fluency both in English and French, after controlling for PA and RAN. However, this result was not duplicated in Greek ( Desrochers et al, 2017 ; Diamanti et al, 2017 ; Manolitsis et al, 2017 ). Thus, it appears that the role of MA is stronger in opaque orthographies characterized by ambiguous spelling–sound correspondence then in transparent orthographies, in which the letter–sound correspondence is direct.…”
Section: Introductionmentioning
confidence: 88%
“…Estes resultados estão de acordo com o encontrado pela literatura (p. ex., Diamanti et al, 2017;Guimarães et al, 2014;Law et al, 2015;Santos & Fernandes, 2016). O desempenho dos participantes em função do sexo não se mostrou relevante para nenhuma das tarefas, apesar de alguns estudos apontarem que em tarefas que utilizam materiais linguísticos, em geral, as meninas apresentam melhor desempenho do que os meninos (Chiu & McBride-Chang, 2006).…”
Section: Discussionunclassified
“…Em geral, os estudos têm demonstrado que: a consciência morfológica contribui de forma única para o desempenho em compreensão; pode estar alterada em grupos de disléxicos ou de pessoas com problemas de aprendizagem; e o uso de programas de treinamento pode proporcionar resultados melhores em compreensão leitora (p. ex., Diamanti et al, 2017;Law, Wouters, & Ghesquière, 2015;Li, Dronjic et al, 2017;Lyster, Lervåg, & Hulme, 2016;Manolitsis, Grigorakis, & Georgiou, 2017;Tighe & Schatschneider, 2016b). Corroborando esses achados, uma meta análise recente (Tighe & Schatschneider, 2016a) Tendo em vista a importância da consciência morfológica para os processos de alfabetização e desempenho em leitura e escrita (Mota, 2009), assim como da importância da avaliação de diferentes habilidades metalinguísticas para se investigar possíveis dificuldades em habilidades de ordem superior (como a compreensão da leitura) e traçar planos diagnósticos e interventivos (Spinillo, Cloze e em tarefas de consciência morfológica, investigando os efeitos da idade e do ciclo escolar nesses construtos; (2) investigar a correlação entre estas habilidades e o poder preditivo da consciência morfológica no desempenho em compreensão leitora.…”
Section: Introductionunclassified
“…Recently, the development of reading abilities of Greek children has intensively attracted research attention (e.g. Anastasiou & Protopapas, 2015;Desrochers, Manolitsis, Gaudreau, & Georgiou, 2017;Diamanti, Mouzaki, Ralli, Antoniou, Papaioannou & Protopapas, 2017;Nikolopoulos, Goulandris, Hulme & Snowling, 2006;Porpodas, 2012;Protopapas, Simos, Sideridis, & Mouzaki, 2012). Researchers have focused on how Greek children acquire reading and investigated the language specific effects on reading acquisition in order to develop assessment tools.…”
Section: Introductionmentioning
confidence: 99%